Case report: pathological complete response after S-1/oxaliplatin regimen combined with trastuzumab and tislelizumab in patients with locally advanced gastric cancer - Zhu, Chenglou; Li, Yaoqi (Frontiers in Oncology, 2024)
BackgroundThe efficacy of a regimen combining Tegafur, Gimeracil and Oteracil Potassium Capsules (S-1), oxaliplatin (SOX) with trastuzumab and tislelizumab chemotherapy for advanced gastric cancer (GC) has not been reported.Case summaryA 56-year-old male was diagnosed with GC combined with peripheral lymph node metastasis. The patient received neoadjuvant chemotherapy, including SOX, tislelizumab and trastuzumab. After 4 cycles of chemotherapy, the tumor shrank significantly, and radical surgery was performed with good clinical results. To date, the patient has been followed up for 6 months with no significant side effects.ConclusionIn this study, the patient received combination chemotherapy with SOX trastuzumab and tislelizumab and successfully underwent radical surgery with good clinical outcomes. Combined SOX with trastuzumab and tislelizumab may be an effective neoadjuvant chemotherapy regimen.